OPTIMASI PENGELOLAAN PERSEDIAAN BARANG MENGGUNAKAN METODE PERPETUAL PADA APLIKASI INVENTORY DI PT. VISI KARYA PRAKARSA - Mohammad Bayu Anggara; Iyus A Muslimin (Program Studi Teknik Informatika FTI UNIBBA, 2023)
This research focuses on the design and implementation of an inventory application by applying the perpetual method. The inventory application is a tool created with the aim of producing digital reports on the flow of incoming and outgoing goods. This study was conducted at PT Visi Karya Prakarsa that the inventory recording system is still manual with problems such as data input errors, overstocking and understocking, late deliveries from suppliers, and problems with damaged goods. Therefore, the purpose of this research is to design an inventory entry and exit system at PT. Visi Karya Prakarsa that is able to generate inventory reports, while overcoming the problem of inaccuracies in the organization of the procurement cycle. A quantitative approach is used in this research, with the application of the SDLC waterfall development model to design the application. The results of this study are expected to provide benefits in the form of inventory applications using the perpetual method.